2018
DOI: 10.1080/03007995.2018.1502166
|View full text |Cite
|
Sign up to set email alerts
|

Adenocarcinoma histology is a poor prognostic factor in locally advanced cervical cancer

Abstract: Adenocarcinoma histology negatively impacts OS and RFS for advanced cervical cancer. Histology-specific therapy may be an opportunity for survival improvement in these women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 42 publications
0
16
0
1
Order By: Relevance
“…Cervical cancer patients with a low expression of ITM2A were more likely have adenocarcinoma or adenosquamous carcinoma, while cervical cancer patients with a high expression of ITM2A tended have squamous carcinoma. Compared with squamous cell carcinoma, cervical adenocarcinoma has a worse outcome [48,49]. Our study found that the low expression of ITM2A was associated with poor prognosis and cervical…”
Section: Discussionmentioning
confidence: 50%
“…Cervical cancer patients with a low expression of ITM2A were more likely have adenocarcinoma or adenosquamous carcinoma, while cervical cancer patients with a high expression of ITM2A tended have squamous carcinoma. Compared with squamous cell carcinoma, cervical adenocarcinoma has a worse outcome [48,49]. Our study found that the low expression of ITM2A was associated with poor prognosis and cervical…”
Section: Discussionmentioning
confidence: 50%
“…The influence of histology on the prognosis of cervical cancer has long been debated [ 19 , 20 ]. A study reported that adenocarcinoma had negative relation with the survival of advanced stage cervical cancer [ 21 ]. Tough FIGO stage system was widely used in clinical activities, the survival time of cervical cancer was diverse even with identical stage.…”
Section: Discussionmentioning
confidence: 99%
“…According to many studies, patients with ADC exhibit worse survival outcomes than patients with SCC [ 17 18 ]. The Japan Society of Obstetrics and Gynecology collected and analyzed data from 15,698 patients with cervical cancer, and found that patients with SCC had a significantly better prognosis than patients with ADC (p=0.004); the 5-year OS rates were 80.4% and 75.7% for patients with SCC and ADC, respectively [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Distant recurrence had poorer survival compared with patients with locoregional or lymphatic recurrence. Some investigators have suggested that ADC is a distinct clinical entity from SCC and may be different at the molecular level [ 17 20 ]. This situation, taken as a whole, our results suggest that ADC associated with worse survival than SCC even after PSM.…”
Section: Discussionmentioning
confidence: 99%